Answer:
For every change in x by -6, there is a corresponding change in y by -4
Step-by-step explanation:
Given
x ---- y
9 --- 4
3 --- 0
-3 -- -4
-9 -- -8
Required
Determine the rate of change
To do this, we simply get an expression for the slope.
Take any two corresponding x and y values.
[tex](x_1,y_1)= (9,4)[/tex]
[tex](x_2,y_2)= (3,0)[/tex]
The slope (m) is:
[tex]m = \frac{y_2 - y_1}{x_2 - x_1}[/tex]
This gives:
[tex]m = \frac{0 - 4}{3 - 9}[/tex]
[tex]m = \frac{- 4}{-6}[/tex]
This can then be represented as:
[tex]\frac{y_2 - y_1}{x_2 - x_1} = \frac{- 4}{-6}[/tex]
It means that:
For every change in x by -6, there is a corresponding change in y by -4